The Effect of Emotional Arousal on Inhibition of Return Among Youth With Depressive Tendency - Zhang, Liwei; Fan, Huiyong; Wang, Suyan; Li, Hong (Frontiers in Psychology, 2019)
The occurrence and development of depressive symptoms were thought to be closely related to excessive attention to negative information. However, the evidences among researchers were inconsistent on whether negative emotional information could induce attention bias in depressed individuals. One possible hypothesis is that the arousal level of stimuli regulates the attention bias of depressed individuals to negative emotional stimuli. In the current study, we directly assessed the attentional inhibition of depression-tendency individuals to different arousal levels of negative emotional faces. The Center for Epidemiologic Studies Depression Scale (CES-D) was used to distinguish the depression-tendency group from the health group. Thirty-three participants in each group completed a simpler cue-target task that comprised four kinds of experimental conditions, in which group was an inter-subject variable, while cue validity, arousal level and stimulus onset asynchrony were internal variables. By subtracting the reaction time under the valid cue from the reaction time under the invalid cue, we got the magnitudes of inhibition of return (IOR), which reflected the effective suppression of previously noticed irrelevant information. We found that, in health group, the IOR effect was smaller at high arousal level than at low arousal level. This means that even in the normal population, higher arousal level of negative emotional information could weaken the individual's attention inhibition ability. While in the depression-tendency group, the IOR effect only appeared at low arousal level condition, but in the high cue condition it showed the reversal pattern, that was, the cue effect. These results indicated for the first time that the attention bias of depressive individuals to negative emotional stimuli was influenced by the arousal level of stimuli, and the negative stimuli with high arousal level were more difficult to suppress.